2004
DOI: 10.1111/j.1445-1433.2004.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

Delay in surgery for acute appendicitis

Abstract: The present prospective study concludes that morbidity caused by acute appendicitis correlates directly with delay in treatment. In the majority of cases the delay in treatment is predominantly caused by patient related factors. The negative appendicectomy rate can be reduced by close observation of cases with clinical uncertainty without increasing the morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 7 publications
9
35
0
1
Order By: Relevance
“…There has been a continuous debate concerning whether patient-related or physician-related delays in diagnosis is the main cause of perforation. The current findings agree with previous studies [3, 5, 9, 14] indicating that perforation of the diseased appendix was largely determined by the pre-hospital phase of the patient’s illness, although some authors stress the importance of physician delay as a cause of advanced appendicitis [2]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There has been a continuous debate concerning whether patient-related or physician-related delays in diagnosis is the main cause of perforation. The current findings agree with previous studies [3, 5, 9, 14] indicating that perforation of the diseased appendix was largely determined by the pre-hospital phase of the patient’s illness, although some authors stress the importance of physician delay as a cause of advanced appendicitis [2]. …”
Section: Discussionsupporting
confidence: 82%
“…No less than 20–30% of patients have atypical symptoms, signs or laboratory findings [1]. A delay in diagnosis due to physician-related factors has been reported [1, 2] but more frequently patient-related factors have been determined the most important cause of delay in treatment [3,4,5]. A close relation between the degree of inflammation, or perforation, of the appendix and duration of inflammation has been assumed [6]; however, this view has been challenged [7, 8] by the argument for two main types of appendicitis – one that is prone to perforation and one that is not.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings were consistent with the results of previous study, which showed that, appendix perforation mostly depended on the duration of the pre-admission [3,5,9,13]. However, some authors have been emphasizing the importance of physician-related delay of diagnosis, as a cause of advanced appendicitis [2].…”
Section: Discussionsupporting
confidence: 92%
“…At least 20% to 30% of the patients have atypical symptoms, signs or laboratory findings. Although physician-related diagnostic delays have been reported [1,2], patient-related factors constitute the main reason of delays [3][4][5]. It is assumed that there has been a close relation between the level of inflammation or perforation and duration of inflammation [6], however, this idea has been declined with an argument among two main appendicitis types with and without tendency to perforation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for transfer were Vascular (7), Urological (6), Neurosurgical (4), General surgical including obesity (4), postoperative instability (3), ENT (2), ERCP (2), maxillofacial (2) and paediatric surgery (2). Only eighteen of these patients were not subject to a clinically significant delay.…”
Section: Rs010 Surgical Retrieval From a Rural Referral Hospital: Commentioning
confidence: 99%